Impact of COVID-19 lockdown on medical education in India and its scope on distance learning - Kondeti Madhavi; Pasupuleti Visweswara Rao (Penerbit UMS, 2021)
The year 2020 was frightened with fight against unprecedented Coronavirus Disease-19 (COVID-19) pandemic situations which impacted extreme changes in everyone’s lives. Particularly healthcare system was not ready to tackle public health emergency on immediate declaration of COVID-19 outbreak by World Health Organization (WHO), later the lockdown situations have helped a lot to tackle the situations worldwide. Coming to the medical education in India, there are 272 government medical colleges with teaching hospitals and 260 private medical colleges including deemed universities in India, a good asset to India. Total of 76,928 of Bachelor of Medicine, Bachelor of Surgery (MBBS) students were getting admitted in to the colleges every year with an average intake of 150- 250 students per college and per year. The COVID-19 pandemic has strengthened distance & e-Learning worldwide. Distance & e-Learning is defined as application of computer technology to deliver training, including technology-supported learning either online, offline, or both (Shivangi, D. 2020). This technology has also helped a lot to the medical education across the world including India.